A condição da mulher negra na literatura brasileira em Úrsula, Casa de Alvenaria e Um defeito de cor - Dalcol, Mônica Saldanha (2020)
The present thesis dissertation aims to compare three narratives of black Brazilian writers that span three centuries: Úrsula (1859) by Maria Firmina dos Reis, 19th century, Casa de Alvenaria (1961) by Carolina Maria de Jesus, 20th century, and Um defeito de cor (2006) by Ana Maria Gonçalves, 21st century. We did a comparative study of these three works with its foundations on the concept of intersectionality, present in black feminism, whereby we need to take into account black women experiences through the categories of gender, race and class. Therefore, we will focus, mainly, on the issue of Brazilian black female authorship, through a discussion and problematization of silencing attempts, which stigmatize and marginalize the literary projects developed by black writers present in the corpus of this work. We seek to clarify that the literary production of black authors points to an ethical opening, from the fictional plane, capable of rewriting Brazilian literature, as well as the very idea of nation.